Efficiency differentials in resource-use among smallholder cassava farmers in southwestern Cameroon. Issue 3 (2nd April 2020) - Molua, Ernest L.; Tabe-Ojong, Martin Paul; Meliko, Majory O.; Nkenglefac, Miranda Fotabong; Akamin, Ajapnwa
ABSTRACT: Cassava has been identified as one of the staples that can reduce food security and help achieve the Sustainable Development Goal of "zero hunger". This article aims to estimate the efficiency levels of cassava producers in the Southwest region of Cameroon and to identify factors that account for efficiency differentials. The results show that, on average, cassava farmers are 64% technically efficient under the constant returns to scale and 96% under the variable returns to scale assumptions. The difference between the two models suggests the existence of scale inefficiency. Results also show that variables such as farm size, experience and land-use intensity are factors that significantly enhance the efficiency of cassava producers. A key recommendation is the need for policies that ensure increased access to agricultural land as well as secure tenure for cassava producers.